K-GENERALIZED MITTAG-LEFFLER STATISTICAL DISTRIBUTION - Daiya, Jitendra; Ram, Jeta (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The object of this paper is to investigate the Statistical density of k- generalized Mittag-Leffler function. Representations of such relations are obtained in terms of statistical density.Â 